Factors influencing readiness towards halal logistics among food-based logistics players in Malaysia - Ahmad Tarmizi, Hazwani; Kamarulzaman, Nitty Hirawaty; Abd Latif, Ismail; Abd Rahman, Azmawani (Elsevier, 2014)
Logistics is part of supply chain which involves many business entities such as suppliers, manufacturers, distributors and retailers. All these entities will work together to acquire raw materials and transform them into final products. Halal logistics is an approach to avoid contamination of perishable, raw materials and food products during transportation or distribution activities. It is also to avoid products missed information and to ensure that Muslim consumers will receive and consume only the Halalan Toyibban products. In Malaysian Standard for Halal Logistics (MS 2400:2010), halal logistics requirements according to Shariah law are including the requirement of logistics providers for transportation, warehousing and retailing. The requirement usually involved from processing to handling, distribution, storage, display, serving, packaging and labeling. There are few concerns regarding the implementation of halal logistics among logistics players. First, there is concern whether these players follow all guidelines and standards for halal logistics. Second, there is concern whether these players segregate their workers and facilities in producing and distributing activities for halal and non-halal products. This study seeks to investigate factors that influence readiness towards halal logistics among food-based logistics players. Face-to-face interviews were carried out with 156 managers representing logistics companies located in Peninsular Malaysia. Factor analysis was carried out to analyze the data obtained from the managers. The results revealed that support from management, enforcement of Halal Assurance System (HAS), environments controls, employee acceptance and company vision to change were the factors that influenced readiness towards halal logistics.